Relación entre clima institucional y desempeño docente en instituciones educativas de inicial de la Red N° 9 - Callao - Mendoza Aedo, Ada Herlinda (2011)
The research had as purpose establish the relationship between the institutional climate and the teacher performance in educational institutions of initial of the network number 9-Callao. The research is a correlational type. The study sample was applied a 45 teachers. The questionnaire was also applied to 205 parents to know their opinion to teacher performance of their teachers, a questionnaire to each variable of Likert scale. Whose data processing has allowed get the following results: -General level there is a relationship (0.537) significant between institutional climate and teachers performance. -Especific level there is a high relationship (0.504) and significant between institutional behavior in organizational capacity (0.448) in institutional dynamics (0.524).